Answer:
(x, y) → (x + 4, y - 3)
h = 4
k = -3
Explanation:
Given points:
- M = (3, 4)
- M' = (7, 1)
- T = (-2, 3)
- T' = (2, 0)
Given translation:
(x, y) → (x+h, y+k)
To find the value of h, subtract the x-values of points M and T from the x-values of points M' and T':
![\begin{aligned}\implies h&=x_(M')-x_M\\&=7-3\\&=4\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/oaa3aywty0v814i1zgv3ezj3koen6unfpp.png)
![\begin{aligned}\implies h&=x_(T')-x_T\\&=2-(-2)\\&=4\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/74avaaczfa4h7sx08u7jb1wm2v6td7l7x5.png)
To find the value of k, subtract the y-values of points M and T from the y-values of points M' and T':
![\begin{aligned}\implies k&=y_(M')-y_M\\&=1-4\\&=-3\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/cc61k9gu2ylw33lzvnzdy80anjgivdujb5.png)
![\begin{aligned}\implies k&=y_(T')-y_Y\\&=0-3\\&=-3\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/high-school/veqxhuldzqhwzxe9wh0gxm4sugt740orc6.png)
Therefore the algebraic description of the translation is:
(x, y) → (x + 4, y - 3)